Effectiveness of a LATCH-Based Midwife Training Program on Breastfeeding Attachment and Mastitis Risk: A Randomized Controlled Trial - mutiaradwiyanti; Siagian, Nurul Aini; Purba, Tetty Junita; Ariani, Peny; lubis, kholilah (Jurnal Kesehatan - STIKes Prima Nusantara, 2026)
Background: Most literature indicates that direct contact between health workers and postpartum mothers, even when the mother is not in the hospital, is a significant intervention. In this model, health workers face time and distance constraints in implementing the intervention. This study proposes an intervention model based on education and additional training for midwives. This improvement in midwives' knowledge and skills is expected to significantly contribute to breastfeeding practices. Objective: This study aims to analyze the effectiveness of LATCH score-based midwife training on breastfeeding attachment quality (latch) and reducing the risk of mastitis. Methods: This study involved 130 postpartum mothers at Sembiring Hospital, North Sumatra Province, Indonesia. Randomization was conducted at the level of the mothers, who were allocated to the midwives on duty. Data collection was carried out from June to August 2025 and was divided into three periods. Data were analyzed using descriptive statistical methods, the Mann–Whitney test, and the Chi-Square test. Results: The breastfeeding practice profiles of the study participants have been described. The mean LATCH scores for each period were 6.16 (±1.69), 7.13 (±1.71), and 7.47 (±1.70). Statistically significant differences in LATCH scores were found between the intervention and control groups at each period. A significant association between group type and mastitis incidence was observed only in the early postpartum period and was not significant after maternal discharge. Conclusion: Training is effective in the short term, but for long-term impact a more comprehensive model is needed.